Mapping the interplay among cognitive biases, emotion regulation, and depressive symptoms. Issue 4 (19th May 2017) - Everaert, Jonas; Grahek, Ivan; Duyck, Wouter; Buelens, Jana; Van den Bergh, Nathan; Koster, Ernst H. W.
ABSTRACT: Cognitive biases and emotion regulation (ER) difficulties have been instrumental in understanding hallmark features of depression. However, little is known about the interplay among these important risk factors to depression. This cross-sectional study investigated how multiple cognitive biases modulate the habitual use of ER processes and how ER habits subsequently regulate depressive symptoms. All participants first executed a computerised version of the scrambled sentences test (interpretation bias measure) while their eye movements were registered (attention bias measure) and then completed questionnaires assessing positive reappraisal, brooding, and depressive symptoms. Path and bootstrapping analyses supported both direct effects of cognitive biases on depressive symptoms and indirect effects via the use of brooding and via the use of reappraisal that was in turn related to the use of brooding. These findings help to formulate a better understanding of how cognitive biases and ER habits interact to maintain depressive symptoms.